LITERATURE REVIEW: MEKANISME RESISTENSI ANTIBIOTIK PADA BAKTERI PATOGEN - Anggia Putri, Cindy (Jurnal Biogenerasi, 2026)
Antibiotic resistance is an increasing health problem that poses a serious challenge to the treatment of infectious diseases, particularly in tropical regions such as Indonesia. Resistant pathogenic bacteria reduce the effectiveness of antibiotic therapy and increase the risk of treatment failure. This article aims to review the mechanisms of antibiotic resistance in pathogenic bacteria using a literature review approach. Relevant national and international scientific articles were analyzed. The results indicate that antibiotic resistance can be classified into intrinsic and acquired resistance, with major mechanisms including antibiotic inactivation, modification of antibiotic targets, decreased membrane permeability, and efflux pump activity. Common pathogenic bacteria associated with antibiotic resistance include Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa. In conclusion, understanding antibiotic resistance mechanisms is essential for developing effective control strategies and promoting rational antibiotic use.